Cardiovascular manifestations and echocardiographic findings in pediatric multisystem inflammatory syndrome associated with COVID-19 (MIS-C): A retrospective study - J, Jashvanth H; Rudrappa, Sudha; Patagar, Pratibha Manjunath (Indian Journal of Child Health, 2021)
Background: The multisystem inflammatory syndrome in children (MIS-C) has been described recently during COVID-19 pandemic. It is a delayed post-infectious response with a lag time of 4–6 weeks following the exposure to severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), involving multiple systems which is being increasingly reported worldwide. Aim: The study aims to investigate and report the cardiovascular manifestation and echocardiographic findings in pediatric patients diagnosed with MIS-C. Materials and Methods: The present study is a retrospective analysis of clinical data gathered from 40 admitted children diagnosed with MIS-C. The study was conducted for 1 year (from 1st June 2020 to 30th May 2021) at Cheluvamba Hospital, a tertiary care center attached to Mysore Medical College And Research Institute, Mysore, Karnataka. Results: Out of 40 children, 21 (52.5%) had manifestation of cardiovascular system in the form of shock, requiring ionotropic support and care at the Intensive Care Unit. Among them, 90% patients show elevated cardiac biomarker (Troponin T), 33.3% had two-dimensional echocardiographic (2D echo) findings in which 9.5% show coronary artery dilatation and 23.8% show left ventricular hypertrophy. Conclusion: MIS-C is a hyperinflammatory syndrome related to SARS-CoV-2 infection. Cardiac involvement is evidenced by perturbation of cardiac chamber size, function, coronary artery abnormalities, and elevated cardiac biomarker. Though, most of the patients responded to the initial treatment and recovered, there is scarcity of data regarding long-term cardiovascular complication.